Molecular characterization of bacteria and kleptoplast within Virgulinella fragilis - Tsuchiya, Masashi; Toyofuku, Takashi; Takishita, Kiyotaka; Yamamoto, Hiroyuki; Collen, John; Kitazato, Hiroshi (Anuário do Instituto de Geociências, 2006)
Abstract